Methods in Dating and Other Applications using Luminescence - Feathers, James K. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Trapped charge dating is a commonly used chronological tool in Earth Sciences and Archaeology. The two principle methods are luminescence dating and electron spin resonance. Both are based on stored energy produced by the absorption of natural radioactivity in common minerals such as quartz and feldspars, and in some biological materials such as tooth enamel. Methodological developments in the last 20 years have substantially increased the accuracy and precision of these methods. This compilation offers a taste of the recent research into both method and applications.